"With a connection to the land, our spirit is strong" Tlicho traditional knowledge of climate change and impacts for caribou hunting: implication for traditional knowledge research - Jacobsen, Petter (Author); Johnson, Chris (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2012)
My research was to document the Elders knowledge of climate change and the impacts on caribou hunting. The Elders explained starting in the 1960-70s the weather has become warmer and drier leading to a change in hunting locations and modified hunting times. Changes to wind patterns as well as changes to snow and ice conditions have caused uncertain weather predictions and increased the community members' focus on safety. The consequence of these impacts of climate change is an increased reliance on gas and money to sustain hunting. The Tlicho Elders tied these environmental changes to human-environment interactions and interpreted these climate changes with the larger process of social changes within modern society. Based on such social perspectives of the environment, I argue that Traditional Knowledge research of climate change needs to be based on an Indigenous perception, and I provide recommendations to indigenize climate change research with sub-arctic Indigenous peoples. --P. 2. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1779636